Supervision Strategies Used to Support Spanish-Speaking Bilingual Counselors - Heather Trepal; Angelica Tello; Maria Haiyasoso; Nancy Castellon; Jessenia Garcia; Cristina Martinez-Smith (Teaching and Supervision in Counseling, 2019)
Multilingual diversity is increasing in the United States, with Spanish being the nation’s second most common spoken language (U.S. Census, 2016). In response, more Spanish-speaking bilingual counselors are providing bilingual counseling services. These counselors face unique experiences related to the constellation of language, culture, and professional development. Yet, supervisors are working with these counselors and little is known about their experiences or specific supervision strategies. This article presents the results of interviews with supervisors (N=8) of Spanish-speaking bilingual counselors regarding their supervision strategies. Implications for supervisors are provided.
Keywords: Supervision; bilingual; strategies